SOCIOECOLOGICAL AND HYDROLOGICAL DYNAMICS IN THE UPPER CAQUETÁ RIVER BASIN (2013–2023): EXTREME CLIMATE, LAND-USE TRANSFORMATIONS, AND SURFACE WATER DYNAMICS (Interdisciplinary Studies Journal, 2026)
This article aims to analyze and interpret vegetation cover, land-use type (natural or anthropogenic), and hydrological behavior data provided by the MapBiomas Colombia platform for the upper Caquetá River basin, in order to examine the state of these variables over a 10-year period, from 2013 to 2023. This approach seeks to provide a general overview of the basin’s water dynamics and to identify associated environmental challenges
Keywords: Land Cover; Caquetá River; MapBiomas; Hydrological Dynamics; Amazon